Policy change, public attitudes and social citizenship : does neoliberalism matter? - Humpage, Louise (JSTOR EBA., 2015)
Neoliberal reforms have seen a radical shift in government thinking about social citizenship rights around the world. But have they had a similarly significant impact on public support for these rights? This book traces public views on social citizenship across three decades through attitudinal data from New Zealand, the UK, and Australia. It argues that support for some aspects of social citizenship slipped more significantly under some political regimes than others, and that limited public resistance following the financial crisis of 2008-2009 further suggests the public accepted these neoliberal values.